2017
DOI: 10.1111/anae.13969
|View full text |Cite
|
Sign up to set email alerts
|

Arterial to end‐tidal carbon dioxide difference in children undergoing mechanical ventilation of the lungs during general anaesthesia

Abstract: Capnography (ETCO ) is routinely used as a non-invasive estimate of arterial carbon dioxide (PaCO ) levels in order to modify ventilatory settings, whereby it is assumed that there is a positive gap between PaCO and ETCO of approximately 0.5 kPa. However, negative values (ETCO > PaCO ) can be observed. We retrospectively analysed arterial to end-tidal carbon dioxide differences in 799 children undergoing general anaesthesia with mechanical ventilation of the lungs in order to elucidate predictors for a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…1 Furthermore, negative arterial to endtidal carbon dioxide differences (ETCO 2 > PaCO 2 ) in children have been reported to erroneously lead to overestimation of ETCO 2 with subsequent risk of unrecognized hypocapnia. 21 In agreement with previous studies, the current animal model demonstrated a decrease in PtO 2 during hypocapnia. [9][10][11][12][13][14][15] The observed effect in the present study is even more convincing when the simultaneous increase in P a O 2 caused by hyperventilation is taken into account.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1 Furthermore, negative arterial to endtidal carbon dioxide differences (ETCO 2 > PaCO 2 ) in children have been reported to erroneously lead to overestimation of ETCO 2 with subsequent risk of unrecognized hypocapnia. 21 In agreement with previous studies, the current animal model demonstrated a decrease in PtO 2 during hypocapnia. [9][10][11][12][13][14][15] The observed effect in the present study is even more convincing when the simultaneous increase in P a O 2 caused by hyperventilation is taken into account.…”
Section: Discussionsupporting
confidence: 93%
“…Hyperventilation with subsequent hypocapnia is an often‐observed accidental disturbance of physiological homeostasis during anesthesia and is sometimes even deliberately induced . Furthermore, negative arterial to endtidal carbon dioxide differences (ETCO 2 > PaCO 2 ) in children have been reported to erroneously lead to overestimation of ETCO 2 with subsequent risk of unrecognized hypocapnia …”
Section: Discussionmentioning
confidence: 99%
“…Parameters provided by respiratory gas monitoring, such as respiratory gas flow, are required to monitor the saturation level of the patient (21,22). In a study that retrospectively investigated the differences in arterialend-tidal carbon dioxide in 799 pediatric patients undergoing general anesthesia with ventilation, it was determined that the decrease in PaCO2 was strongly related to the decrease in the PaCO2-ETCO2 difference (23). 29.5% and 32.7% of the nurses were found to have no knowledge about the function of the capnograph device and its effectiveness during the mechanical ventilator respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Capnography is considered the gold standard, both to determine correct placement of a de nitive airway and to guide ventilation during emergency care [9,10]. The assumed correlation between EtCO 2 and PaCO 2 has been known to be accompanied by a tension difference of CO 2 ranging anywhere between 0.26 and 0.66kPa (2 and 5 mmHg) in otherwise healthy individuals undergoing anesthesia [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%